The Effect of the Student Teams Achievement Division (STAD) Learning Method on Student Learning Outcomes in Citizenship Education for Grade IV students at AL Khansa Rengat Elementary School - Ningrum Melihayatri; Udin Syaefuddin Sa’ud (International Conference on Elementary Education, 2023)
This study aims to determine the effect of the STAD type of cooperative learning model. The method used is descriptive quantitative. Data obtained from tests and questionnaires. The source of the data from this study was a sample of 31 from the control class and 31 from the experimental class. The results of this study are that learning before using the Student Teams Achievement Division (STAD) learning model is still monotonous learning and lack of activity in class so that it affects student learning outcomes. but after applying the Student Teams Achievement Division (STAD) learning model it can be stated that it has increased. This is evidenced by Based on the calculations that have been done, the average value of the control class is 85.07 and the average value of the experimental class is 90.48. Based on these average values, it can be seen that the average experimental class = 90.48 > average control class = 85.07.